Case Report: Diverticulum of the left ventricular outflow tract: multimodal imaging - Chen, Qiqing; Liu, Lili; Cao, Yiqiu; Chen, Pian; Zhong, Wenjin; Jing, Xiangxiang (Frontiers in Cardiovascular Medicine, 2024)
The left ventricular diverticulum (LVD) is a rare congenital heart disease commonly discovered during examinations. Herein, we report a LVD on the lateral wall of left ventricular outflow tract. A case of a 22-year-old female patient who visited our hospital with complaints of shortness of breath, accompanied by vomiting, cough, and lower limb and facial edema and was diagnosed with “aortopulmonary septal defect” using transthoracic echocardiography. After cardiac surgery and postoperative pathology, she was confirmed with a LVD. The patient's clinical symptoms, multimodal imaging examination, and treatment methods were used to assess this case.